Benefits of daytime napping opportunity on physical and cognitive performances in physically active participants: A systematic review - Souabni, M.; Hammouda, O.; Romdhani, M.; Trabelsi, K.; Ammar, A.; Driss, T. (Sports Medicine, 2021)
Background: Evidence suggests that athletes often experience chronic sleep disturbance. Napping is widely recommended as a safe and non-invasive intervention to counteract the negative effects of partial sleep deprivation. However, systematic reviews on the benefits of napping have yet to be undertaken. Objective: (i) To evaluate the effectiveness of diurnal napping opportunities on athletes` physical and cognitive performance and (ii) to outline how aspects of the study design (i.e., nap duration, exercise protocol, participants` fitness level and previous sleep quantity) can influence the potential effects of napping through a systematic appraisal of the literature. Methods: This systematic review was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. PubMed, Web of Science and SCOPUS databases were searched up to June 2020 for relevant studies investigating the effect of napping on physical and cognitive performances in physically active participants. Fourteen strong-quality and four moderate-quality (mean QualSyst score = 75.75 ± 5.7%) studies met our inclusion criteria and were included in the final sample (total participants: 158 physically active and 168 athletes). Results: Most studies (n = 15) confirmed the beneficial effects of napping and showed that diurnal napping improved short-term physical performance (n = 10), endurance performance (n = 3) and specific skills performance (n = 2). Two studies showed no significant napping effect and only one study showed reduced sprint performance following diurnal napping. Moreover, napping improved reaction time (n = 3), attention (n = 2) and short-term memory (n = 1) performances. Importantly, "replacement naps" improved both physical and cognitive performance regardless of the type of exercise. However, "prophylactic naps" improved only jump, strength, running repeated-sprint, attention and reaction time performances. In addition, this systematic review revealed that longer nap opportunities (i.e., 90 min) resulted in better improvement of physical and cognitive performance and lower induced fatigue. Conclusions: A diurnal nap seems to be an advantageous intervention to enhance recovery process and counteract the negative effect of partial sleep deprivation on physical and cognitive performance. Particularly, to optimize physical performances of athletes experiencing chronic lack of sleep, findings from the included individual studies suggest 90 min as the optimal nap duration. Diurnal napping may be beneficial for athletes but this benefit should be viewed with caution due to the quality of the evidence, risk of bias and the limited evidence about napping interventions.